Demonstration of the direct impact of ketamine on urothelium using a tissue engineered bladder model - Bureau, Michel (Can Urol Assoc J, 2015)
INTRODUCTION: Ketamine is a common recreational drug. Severe lower urinary tract symptoms associated with its consumption have been reported, but little is known about the involved mechanisms. The effect of ketamine, which is excreted in urine, was evaluated by its application on an in vitro three-dimensional human tissue-engineered bladder model composed of an urothelium and a submucosa. METHODS: Human urothelial cells were cultured with medium containing various concentrations of ketamine and harvested at different times to obtain growth curves. Using this model, specific activity of caspase-3 was measured to assess the level of apoptosis induced by ketamine. Finally, a human tissue-engineered bladder model was used. Urothelial cells were plated on a stromal layer made of dermal fibroblasts and incubated at the air/liquid interface to allow their differentiation. Ketamine was then put on the mature urothelium using paper or agarose vectors for 48 hours. RESULTS: The presence of ketamine increased cells’ doubling times from 1.26 days for control to 1.38 days (p = 0.14) and 1.78 days (p < 0.01) for the 0.5 mM and 1.5 mM concentrations, respectively. 5 mM and 10 mM of ketamine led to decline in the major cell population. Exposure to 5 mM ketamine induced apoptosis, confirmed by a 2.5-fold increase in capase-3 specific activity from control (p = 0.03). The structure and cellular cohesion of the urothelium on the three-dimensional model, especially in the intermediate layers, were severely affected in a concentration dependant fashion with both vectors. CONCLUSION: The presence of ketamine in the bladder directly damages the urothelium through the induction of apoptosis.